Pediatric registries at the Food and Drug Administration: design aspects that increase their likelihood of success. Issue 5 (21st December 2015) - Winiecki, Scott K.; Tejero‐Taldo, M. Isabel; Avant, Debbie; Murphy, Dianne; McMahon, Ann W.
Abstract: Purpose: To determine aspects of the design of pediatric registries that contribute to the success of registries conducted as a postmarketing study following approval of drugs or biological products by the US Food and Drug Administration. Methods: Pediatric registries for drugs and biological products were identified by searching the US Food and Drug Administration Postmarketing Requirements and Commitments database. Based on the recruitment of patients, the meeting of predetermined deadlines, and the submission of data, we classified studies as successful, unsuccessful, or unevaluable. Design aspects of successful and unsuccessful registries were examined for commonalities. Results: Thirty‐eight studies were identified, and ten registries met the criteria for successful. Four (40%) successful registries utilized a registry established prior to product approval, and six (60%) were disease‐based. Among unsuccessful registries, none were disease‐based or utilized a pre‐existing registry. Conclusions: Characteristics identified as more common to successful registries included utilizing a disease‐based registry and a registry established prior to product approval. Future studies might examine a larger sample of registries to see if these aspects consistently result in successful studies. Published 2015. This article is a U.S. Government work and is in the public domain in the USA.